2000
DOI: 10.4319/lo.2000.45.4.0881
|View full text |Cite
|
Sign up to set email alerts
|

Towards a complete mass balance and model for PCBs and PAHs in a small rural lake, Cumbria U.K.

Abstract: This paper summarizes the processes of exchange/fluxes for polychlorinated biphenyls (PCBs) and polycyclic aromatic hydrocarbons (PAHs) in a small well-studied rural lake, Esthwaite Water in northwest England. Measurements of PCB and PAH concentrations have been made in rain, air, water, dated sediment cores, and sediment trap samples over a 2-yr study period and used to determine fluxes to and from the lake. A steady state mass balance model was used to construct an input-output budget for the chemicals and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The resulting average sedimentation rate for the core is thus 4.14 ± 2.96 g m -2 day -1 . This rate is comparable to sedimentation rates reported from lakes in the UK (Sanders et al, 1992;Gevao et al, 2000) and in the Great Lakes region in the US (Schneider et al, 2001;Pearson et al, 1997;Baker et al, 1991).…”
Section: Sediment Burial Fluxessupporting
confidence: 82%
“…The resulting average sedimentation rate for the core is thus 4.14 ± 2.96 g m -2 day -1 . This rate is comparable to sedimentation rates reported from lakes in the UK (Sanders et al, 1992;Gevao et al, 2000) and in the Great Lakes region in the US (Schneider et al, 2001;Pearson et al, 1997;Baker et al, 1991).…”
Section: Sediment Burial Fluxessupporting
confidence: 82%
“…PAHs can persist in the environment and they have ability to be transported over long distances (Aamot et al 1996;Halsall et al 2001) they are mainly concentrated to urban and industrial zones, but can also be found in rural areas (Gevao et al 2000;Garban et al 2002) or even in remote regions (Kallenborn et al 1998;Migaszewski 1999). Elevated levels of site specific PAHs are generally found near emission sources and they have been measured extensively during the last few decades in environmental samples, especially in atmospheric particles (Halsall et al 1994;Smith and Harrison 1996).…”
Section: Introductionmentioning
confidence: 98%
“…More recent pollutants include radionuclides, notably caesium‐137, owing to atmospheric weapons testing and reactor accidents (Beresford et al. , 1992), and organic contaminants such as polychlorinated biphenyls and polycyclic aromatic hydrocarbons (Gevao, Hamilton‐Taylor & Jones, 2000).…”
Section: Introductionmentioning
confidence: 99%